MENINGKATKAN DETEKSI SERANGAN PHISHING MELALUI SERANGAN HOMOGRAP - Chairani, Meirza Aulia; Pradhana, Angga Pramodya (MAKSIGAMA, 2025)
Abstract The urgency of this research is to overcome and detect homograph attacks that are currently rampant in Indonesia. The purpose of this research is to know and detect the pattern of homographed attack criminal offense. To determine the criminal liability for the perpetrators of homographed attack criminal offense. The research method used is normative juridical research, which uses a statutory approach and conceptual approach. So that this research looks for patterns of detection of homographed attack perpetrators to trick victims by using writing similar to the original web to trick victims with fake or phishing webs to enter information or personal data, for victims who are not careful about web names and official web url links that are spoofed by the perpetrators of homographed attack crimes, the perpetrators of homographed attack crimes will carry out their actions by breaking into the victim's personal data to enter banking access and accesses that can be broken into by the perpetrators of homographed attack crimes. Criminal sanctions for perpetrators of homograph crimes are temporarily regulated in Article 35 of the ITE Law and get a maximum sanction of 12 years with a fine of 12 billion rupiah contained in Article 51 of the ITE Law and Article 378 of the old Criminal Code and Article 492 of the new Criminal Code with the crime of fraud. The creation of a website by requesting the same form of writing as the original website so that the perpetrator of this homograph crime can make the website look like the original website.